Kundiman a musical and socio-cultural exploration on the development of the Philippine art song - Nicolasora, Michelle (Ann Arbor, Michigan ProQuest, 2014)
This project is a historical research on the development of the Philippine art song, the kundiman. Originating as an oral tradition in a form of a love song, the kundiman became strongly associated with the Philippine revolution, and with nationalism thereafter. This paper puts the kundiman in a center of an exploration on the social milieu, and on its dual roles as a converging point of foreign influences and as a conduit of nationalism.
Thesis (Ph.D. Musical Arts)--The University of Memphis.
Keywords: Songs, Philippine -- 29th century -- History and criticism; Kundiman